Proceedings of the 8th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design: Dri 2015
DOI: 10.17077/drivingassessment.1564
|View full text |Cite
|
Sign up to set email alerts
|

Linking GPS Data to GIS Databases in Naturalistic Studies: Examples from Drivers with Obstructive Sleep Apnea

Abstract: Summary:In naturalistic studies, it is vital to give appropriate context when analyzing driving behaviors. Such contextualization can help address the hypotheses that explore a) how drivers perform within specific types of environment (e.g., road types, speed limits, etc.), and b) how often drivers are exposed to such specific environments. In order to perform this contextualization in an automated fashion, we are using Global Positioning System (GPS) data obtained at 1 Hz and merging this with Geographic Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As explained in our previous work (Dawson et al, 2015), each subject’s 25-variable, 10-Hz data file was reduced to an eight-variable, 1-Hz file. These eight variable included GPS coordinates (latitude and longitude), a measure of GPS signal quality, a date/time stamp, and identification variables.…”
Section: Methodsmentioning
confidence: 99%
“…As explained in our previous work (Dawson et al, 2015), each subject’s 25-variable, 10-Hz data file was reduced to an eight-variable, 1-Hz file. These eight variable included GPS coordinates (latitude and longitude), a measure of GPS signal quality, a date/time stamp, and identification variables.…”
Section: Methodsmentioning
confidence: 99%
“…16 In this regard, the results of other studies have emphasized the use of GIS to investigate OSA disorder. 22…”
Section: Introductionmentioning
confidence: 99%
“…16 In this regard, the results of other studies have emphasized the use of GIS to investigate OSA disorder. 22 Studies in the United States have shown that certain areas in a state are prone to sleep problems. Studies on the correlation between neighborhood characteristics and sleep have also shown that geographical patterns are formed locally.…”
Section: Introductionmentioning
confidence: 99%